Polimorfisme Protein Plasma Darah pada Kelinci Rex, Lokal dan New Zealand White (POLYMORPHISM OF BLOOD PLASMA PROTEIN OF REX, LOCAL AND NEW ZEALAND WHITE RABBIT) - Sarfan, Riri; Sutopo, Sutopo; Kurnianto, Edy (Jurnal Veteriner; Vol 18 No 1 (2017)DO - 10.19087/jveteriner.2017.18.1.144, 2017)
The objective of this study was to determine genetic diversity of rabbit by blood plasma protein variance using electrophoresis at loci of pre-albumin ( Pa ), albumin ( Alb ), ceruloplasmin ( Cp ), transferrin ( Tf ), post-transferrin ( P-tf ) and amylase-I ( Am-I ). The blood analysis was performed at the Laboratory of Physiology and Biochemistry, Faculty of Veterinary Medicine, Gadjah Mada University, Yogyakarta. The materials used were 63 blood samples of rex, local and new zealand white (NZW) rabbit, in which the number of sample in each breed was 21, respectively. Materials were taken randomly. The protein bands resulted from electrophoresis were used to calculate the value of the gene frequency. Genetic diversity was determined by using individual heterozygosity (h) and the average heterozygosity (H) formulas. The genetic distance among breeds of rabbits was analyzed by using DISPAN and MEGA 6.06 programs. Chi-square ( X 2 ) was used to test of Hardy-Weinberg Law (HWL) equilibrium. The results showed that the loci of prealbumin ( Pa ), albumin ( Alb ), ceruloplasmin ( Cp ), transferrin ( Tf ), post-transferrin ( P-tf),  and amylase-I ( Am-I ) in rex, local and NZW rabbits were polymorphic. Rex and NZW rabbits had close genetic relationships based on phylogeny tree analysis. Chi-square test showed that rex, local, and NZW rabbits were in HWL equilibrium for locus of  Pa  and  Cp , while at the locus of  Alb ,  Tf ,  P-tf,  and  Am-I  were in HWL unequilibrium. In conclusion, there are genetic variability of six locuses in rex, local, and NZW rabbits. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui keragaman genetik kelinci melalui analisis keragaman protein plasma darah dengan metode elektroforesis pada lokus pre-albumin ( Pa ), albumin ( Alb ), ceruloplasmin ( Cp ), transferin ( Tf ), post-transferin ( P-tf ), dan amylase-I ( Am-I ). Analisis darah dilakukan di Laboratorium Fisiologi dan Biokimia, Fakultas Kedokteran Hewan, Universitas Gadjah Mada, Yogyakarta. Sebanyak 63 sampel darah kelinci rex , lokal dan New Zealand White (NZW) masing-masing sebanyak 21 sampel digunakan dalam penelitian ini. Penentuan kelinci dilakukan dengan metode observasional dengan cara kelinci dipilih secara acak. Pita-pita protein yang dihasilkan dari elektroforesis digunakan untuk menghitung nilai frekuensi gen. Perhitungan nilai ragam genetik ditentukan menggunakan rumus heterosigositas individual (h) dan rataan heterosigositas ( H ). Hubungan dan jarak genetik antar bangsa kelinci menggunakan program DISPAN dan MEGA 6.06. Analisis statistika menggunakan tabel X 2 untuk menguji lokus-lokus dalam keseimbangan Hukum Hardy-Weinberg (HHW). Hasil penelitian menunjukkan bahwa lokus pre-albumin ( Pa ), albumin ( Alb ), ceruloplasmin ( Cp ), transferin ( Tf ), post-transferin ( P-tf ), dan amylase-I ( Am-I ) pada kelinci rex, lokal, dan NZW bersifat polimorfik. Kelinci rex dan NZW memiliki hubungan genetik yang dekat berdasarkan analisis pohon filogeni. Hasil uji X 2 pada kelinci rex, lokal, dan NZW menunjukkan keseimbangan HHW pada lokus Pa  dan Cp , sedangkan pada lokus Alb , Tf , P-tf,  dan Amy-I memiliki keseimbangan HW yang berbeda-beda. Simpulan dari penelitian ini adalah terdapat keragaman genetik enam lokus pada kelinci rex, lokal, dan NZW.
Keywords: rabbit, rex, local, NZW, polymorphism, genetic diversity